In vivo neural regeneration via AAV-NeuroD1 gene delivery to astrocytes in neonatal hypoxic-ischemic brain injury - Miri Kim; Seokmin Oh; Songyeon Kim; Il-Sun Kim; Joowon Kim; Jungho Han; Ji Woong Ahn; Seungsoo Chung; Jae-Hyung Jang; Jeong Eun Shin; Kook In Park (BMC, 2024)
Abstract Background Neonatal hypoxic-ischemic brain injury (HIBI) is a significant contributor to neonatal mortality and long-term neurodevelopmental disability, characterized by massive neuronal loss and reactive astrogliosis. Current therapeutic approaches for neonatal HIBI have been limited to general supportive therapy because of the lack of methods to compensate for irreversible neuronal loss. This study aimed to establish a feasible regenerative therapy for neonatal HIBI utilizing in vivo direct neuronal reprogramming technology. Methods Neonatal HIBI was induced in ICR mice at postnatal day 7 by permanent right common carotid artery occlusion and exposure to hypoxia with 8% oxygen and 92% nitrogen for 90 min. Three days after the injury, NeuroD1 was delivered to reactive astrocytes of the injury site using the astrocyte-tropic adeno-associated viral (AAV) vector AAVShH19. AAVShH19 was engineered with the Cre-FLEX system for long-term tracking of infected cells. Results AAVShH19-mediated ectopic NeuroD1 expression effectively converted astrocytes into GABAergic neurons, and the converted cells exhibited electrophysiological properties and synaptic transmitters. Additionally, we found that NeuroD1-mediated in vivo direct neuronal reprogramming protected injured host neurons and altered the host environment, i.e., decreased the numbers of activated microglia, reactive astrocytes, and toxic A1-type astrocytes, and decreased the expression of pro-inflammatory factors. Furthermore, NeuroD1-treated mice exhibited significantly improved motor functions. Conclusions This study demonstrates that NeuroD1-mediated in vivo direct neuronal reprogramming technology through AAV gene delivery can be a novel regenerative therapy for neonatal HIBI.